High-Resolution MR Imaging of Microadenomas at 1.5 T: Experience with Cushing Disease - Peck, Wallace W.; Dillon, William P.; Norman, David; Newton, T. H.; Wilson, Charles B. (American Journal of Neuroradiology, 1988)
The MR images of 27 patients with clinically and biochemically suspected Cushing disease were evaluated retrospectively in a blinded fashion. The MR interpretation was compared with detailed operative diagrams and operative and pathologic reports. The examinations were performed on a 1.5-T MR system with thin-section sagittal and coronal T1-weighted (short TR/TE) images. Each pituitary half was considered separately (54 “halves”). Twenty-one pituitary halves were considered to have glandular abnormalities on MR. Compared with surgical findings, 17 MR findings were true positives and four were false positives (one pars intermedia cyst, three normal tissue). Of the 33 pituitary halves considered normal on MR, 26 were true negatives and seven were false negatives. MR had an overall sensitivity of 71% and a specificity of 87% for these adrenocorticotropic hormone (ACTH)–secreting pituitary adenomas. A focal glandular hypointensity identified on coronal images was the most sensitive predictor of adenoma location. Sagittal images were not useful in either detection or localization. Upward convexity of the gland and deviation of the stalk were less useful indicators. Abnormalities of the sellar floor were the least reliable. In comparison with the capabilities of CT detection of microadenomas described in the current literature, it appears that high-field thin-section MR of the sella is the most sensitive imaging method for preoperative localization of ACTH-secreting adenomas in patients with Cushing disease.